Computer Vision Syndrome Before and After the SARS-CoV-2 Pandemic: New-Symptom Onset and Workplace Setup of Visual Display Terminals. - Behrens, Thomas; Griemsmann, Stephanie; Hosbach, Ingolf; Wechsler, Konstantin; Weber, Britta; Clarenbach, Claudia; Petersen, Jens; Neubauer, Birger; Ellegast, Rolf; Casjens, Swaantje (Journal of Occupational & Environmental Medicine, 2025)
Objective: This cross-sectional online survey investigated the associations between the setup of visual display terminals (VDT) and the new onset of symptoms associated with computer-vision syndrome (CVS) after the SARS-CoV-2 pandemic. Methods: CVS was assessed by the standardized CVS-Q questionnaire. Items of VDT workplace setup at home were assessed individually as well as by a comprehensive VDT risk score. New onset and exacerbation of CVS symptoms were modeled using logistic regression, adjusting for various confounders. Results: The overall CVS prevalence was estimated as 42.7%. Symptoms associated with oculomotor dysfunction were particularly affected. An inadequate home-office equipment, several variables related to VDT exposure, and an overall inadequate VDT score (odds ratio = 1.78; 95% conflict of interest 1.10–2.78) were associated with increased risks for CVS. Conclusions: To define effective preventive measures will be a major challenge for future ophthalmological research.